TEACHING OF SPEAKING USING ASYNCHRONOUS E-LEARNING APPLICATIONS - Randi; Nurdin; Ana Kuliahana (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2022)
This research aimed to find out the use of asynchronous e-learning applications in teaching speaking and describe students’ perceptions of asynchronous e-learning applications in online English-speaking courses. The data in this research was collected qualitatively by using observation and focus group discussion. The observation was conducted on the use of asynchronous e-learning applications in teaching speaking. The focus group discussions have been done with thirteen students of Tadris English Department, UIN Datokarama Palu, who were taught using asynchronous e-learning in 2020/2021. This research showed that 1) in this asynchronous teaching and learning, lecturer and students use FlipGrid, WhatsApp group, and Google classroom. 2) the students had a positive perception of the use of asynchronous e-learning in online speaking courses, such as independent learning, and becoming more active, whereas the students also have negative perceptions such as lack of interaction and technical support.